KONSEP INTEGRASI ILMU ABDULLAH AHMAD DALAM PENDIDIKAN ISLAM - Budi Johan bujo; Rifma Ghulam Dzaljad (IAIN Pontianak, 2022)
The purpose of this study is to analyze Abdullah Ahmad's thoughts on the Knowledge Integration and its implementation in Minangkabau as well as its implications for the Adabiah School of West Sumatra and other islamic education sector in Indonesia. This research is a historical study that focuses on the memoirs and educational background of Abdullah Ahmad, including his efforts in developing Adabiah School. This Study method with a history approach was employed to analyze data. This study concluded by arguing the following aspects: the past educational experience had considerable influence on Abdullah Ahmad's thoughts in which religious sciences and general sciences were separated. The colonial education system model that harmed muslims deeply left an impression on his thoughts. The study shows that Abdullah Ahmad did not distinguish between religious and general sciences. Instead, he integrated the two groups of knowledge and, at the same time, removed the dichotomy of the two, and his goal was to lift Islamic society from adversity and backwardness. In addition, Abdullah Ahmad's thoughts also promoted equality of access to education between men and women especially for the muslims. Accordingly, Madrasah Adabiyiah organized and based its educational system on this integration idea with high quality and accessible for all. The concept has been adopted and adapted by many parties including the Indonesian government.Keywords: Integration of Knowledge, Abdullah Ahmad, Islamic Education